2012
DOI: 10.1128/jvi.06967-11
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to Acute Mouse Adenovirus Type 1 Respiratory Infection and Establishment of Protective Immunity in Neonatal Mice

Abstract: There is an incomplete understanding of the differences between neonatal immune responses that contribute to the increased susceptibility of neonates to some viral infections. We tested the hypothesis that neonates are more susceptible than adults to mouse adenovirus type 1 (MAV-1) respiratory infection and are impaired in the ability to generate a protective immune response against a second infection. Following intranasal infection, lung viral loads were greater in neonates than in adults during the acute pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
64
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(71 citation statements)
references
References 40 publications
6
64
1
Order By: Relevance
“…IFN-␥ and Pfn play antagonistic roles during chronic myocarditis caused by Trypanosoma cruzi, with Pfn ϩ CD8 ϩ T cells implicated in causing tissue damage and IFN-␥ ϩ CD8 ϩ T cells preventing tissue damage (41). In the current study, we identified robust induction of IFN-␥ in the heart after MAV-1 infection, consistent with previous studies showing induction of IFN-␥ in MAV-1-infected lungs (25,26). During acute MAV-1 respiratory infection of adult mice, CD4 ϩ and CD8 ϩ T cells are the primary producers of IFN-␥ in the lung (24).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…IFN-␥ and Pfn play antagonistic roles during chronic myocarditis caused by Trypanosoma cruzi, with Pfn ϩ CD8 ϩ T cells implicated in causing tissue damage and IFN-␥ ϩ CD8 ϩ T cells preventing tissue damage (41). In the current study, we identified robust induction of IFN-␥ in the heart after MAV-1 infection, consistent with previous studies showing induction of IFN-␥ in MAV-1-infected lungs (25,26). During acute MAV-1 respiratory infection of adult mice, CD4 ϩ and CD8 ϩ T cells are the primary producers of IFN-␥ in the lung (24).…”
Section: Discussionsupporting
confidence: 81%
“…4D), and TNF-␣ (Fig. 4E) were upregulated in the hearts of infected adult mice, but the magnitudes of these responses were substantially lower than and the kinetics were delayed compared to those in neonates, in contrast to our previous findings in the lungs (26). We detected marked increases in the expression of both IL-1␤ (Fig.…”
Section: Mav-1 Infects Primary Cardiac Myocytes Ex Vivo and Hearts Incontrasting
confidence: 55%
See 3 more Smart Citations